2021
DOI: 10.3389/fmicb.2021.646124
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH and Organic Carbon Properties Drive Soil Bacterial Communities in Surface and Deep Layers Along an Elevational Gradient

Abstract: Elevational gradients strongly affect the spatial distribution and structure of soil bacterial communities. However, our understanding of the effects and determining factors is still limited, especially in the deep soil layer. Here, we investigated the diversity and composition of soil bacterial communities in different soil layers along a 1,500-m elevational gradient in the Taibai Mountain. The variables associated with climate conditions, plant communities, and soil properties were analyzed to assess their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 74 publications
4
15
1
Order By: Relevance
“…Interestingly, variation in pH was significantly correlated with spatio‐temporal changes in bacterial communities, resulting in clear distance–decay relationships potentially due to the interplay between pH and bacteria. These results are in line with studies conducted in soil ecosystems, where soil pH and organic carbon have been shown to drive bacterial community assembly (Fierer & Jackson, 2006; Tian et al, 2021; Xiong et al, 2012). However, we cannot disentangle causality here, and it is possible that pH of the sediment could have selected for specific bacteria, or alternatively, certain bacteria could have been the cause of the pH variation of the sediment due photosynthesis and respiration (Malkin & Meysman, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, variation in pH was significantly correlated with spatio‐temporal changes in bacterial communities, resulting in clear distance–decay relationships potentially due to the interplay between pH and bacteria. These results are in line with studies conducted in soil ecosystems, where soil pH and organic carbon have been shown to drive bacterial community assembly (Fierer & Jackson, 2006; Tian et al, 2021; Xiong et al, 2012). However, we cannot disentangle causality here, and it is possible that pH of the sediment could have selected for specific bacteria, or alternatively, certain bacteria could have been the cause of the pH variation of the sediment due photosynthesis and respiration (Malkin & Meysman, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the abundance of Chloroflexi increased rapidly from 90 to 270 days in the soil of B. ischaemum , while in the soil of L. davurica , the Chloroflexi abundance increased rapidly from 90 to 450 days. This occurrence indicates that resource preferences may partially explain the difference in the relative abundance of Chloroflexi when members of this phylum degrade recalcitrant compounds (Tian et al, 2021). Except for the 450 th day of root decomposition of L. davurica , Acidobacteria exhibited nonsignificant differences in abundance during root decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, all groups of microorganisms (bacteria and fungi) assessed using different methods were strongly related to soil properties, which help explaining the differences observed between plots communities. This is unsurprising as many edaphic conditions are co-correlated, and several studies are now beginning to shed light on the composition of different microbial communities and relationships with edaphic properties across various soils [17,81,82]. The effects of land-use change on soil conditions, which drive microbial community composition, was particularly demonstrated through this study, which investigated different grassland regimes between continuous grassland and continuous crop.…”
Section: Influence Of Soil Characteristics In Shaping the Whole Microbial Community And Enzyme Activitiesmentioning
confidence: 95%